2021
DOI: 10.3390/ma14113063
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of the In-Plane Behavior of Masonry Walls: Theoretical vs. Experimental Results

Abstract: In-plane strength of masonry walls is affected by the resistant mechanisms activated in the walls, i.e., related to flexural or shear behavior. The latter one can occur in the walls according to different failure modes depending on both mortar and unit strengths and on the type of assembling, i.e., ‘regular’ or ‘irregular’ texture. In this paper, a critical review of the existing design formulations for the in-plane strength of masonry walls is firstly presented, with important information on the achievable fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Among these, diagonal tension may not be considered a failure (Moretti 2015), and compression at the corner is similar to diagonal compression failure. It is found in numerous literature that most of the infill panel shows sliding shear failure (Seki et al, 2018, Celano et al, 2021, Zovkic et al, 2012 and compression at the center of the panel (Kaya et al, 2018, Essa et al, 2014, Alwashali et al, 2017. Hence only these two failure mechanisms have been considered herein and the compressive strength (𝑓 ) corresponding to sliding shear and compression at the center panel is computed as per equation (1) and equation (2), respectively.…”
Section: Cyclic Compression Strut Selationmentioning
confidence: 99%
“…Among these, diagonal tension may not be considered a failure (Moretti 2015), and compression at the corner is similar to diagonal compression failure. It is found in numerous literature that most of the infill panel shows sliding shear failure (Seki et al, 2018, Celano et al, 2021, Zovkic et al, 2012 and compression at the center of the panel (Kaya et al, 2018, Essa et al, 2014, Alwashali et al, 2017. Hence only these two failure mechanisms have been considered herein and the compressive strength (𝑓 ) corresponding to sliding shear and compression at the center panel is computed as per equation (1) and equation (2), respectively.…”
Section: Cyclic Compression Strut Selationmentioning
confidence: 99%
“…On the other hand, one of the main aspects governing the response of masonry structural elements to horizontal actions is the shear resistance of the walls to in-plane forces [13,14]. Much research has been carried out in recent years to analyze the effect of TRM strengthening in these conditions, and several valuable studies have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral load-carrying capacity and failure mechanism of URM walls are primarily affected by material properties, boundary conditions, precompression stresses, geometrical properties, and wall cross section morphologies [45][46][47][48]. In the case of URM pier-spandrel systems, the coupling effect between the pier and spandrel provides additional complexity to the problem along with the other parameters.…”
Section: Introductionmentioning
confidence: 99%